Doctor-shopping behaviour amongst adult patients attending family medicine clinic Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Ismail, Shaiful Bahari; Hassan, Nor Asmah; Noor, Syed Hatim (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Introduction: Doctor-shopping refers to the changing of doctor without professional referral in a single episode of illness. It leads to some health risk and social problems. Objectives: To determine the prevalence and associated factors of doctorshopping behaviour amongst adult patients attending Family Medicine Clinic (FMC) Hospital Universiti Sains Malaysia (HUSM). Methodology: It was a cross-sectional study conducted on 442 adult patients aged 18 years and above. It was conducted as face to face interview using questionnaires. Data were analysed using SPSS version 11. Results: Fifty-six percents of these patients met our criteria for doctor-shopping patients. Most of the patients went to general practitioners for consultation prior to FMC visit. One-fifth of the respondents went for alternative treatment for the current illness episode. The main reason for changing doctors was due to no improvement of the illness. Doctor-shopping behaviour was found to be significantly associated with older age group and employed patients. Doctorshopping patients were found to be high among married people, females and patients with low education level, but the associations were not significant. The significant associated factors of doctor-shopping behaviour were chronic duration of illness, and advice to seek treatment from somebody. Conclusion: Prevalence of doctor-shopping behaviour amongst adult patients attending FMC was high. It is important to recognise and anticipate problems related to doctor-shopping behaviour. We need to emphasise on the importance of a good doctor-patient relationship, and give accurate explanation and health education to maintain a proper continuity of care.